Rapid Determination of Antibiotic Resistance in Klebsiella pneumoniae by a Novel Antibiotic Susceptibility Testing Method Using SYBR Green I and Propidium Iodide Double Staining - Zhang, Yabin; Fan, Weihua; Shao, Chunhong; Wang, Jiajia; Jin, Yan; Shao, Jing; Zhang, Ying; Wang, Yong (Frontiers in Microbiology, 2021)
Due to the broad-spectrum antibiotic usage and empirical treatments, the pathogenic bacterium Klebsiella pneumonia has shown extremely high detection rates at hospitals with an increasing antibiotic resistance. Therefore, rapid detection of the antibiotic resistance is urgently required and essential for effective treatments. In this study we evaluated the performance of a newly developed method for ultra-rapid detection of antibiotic resistance in 30-60 minutes in K. pneumonia by using the SYBR Green I and propidium iodide (PI) staining. A total of 100 clinical isolates were tested for antibiotic resistance using four different antibiotics (ceftriaxone, cefepime, meropenem, and ciprofloxacin). The results showed that the SYBR Green I/PI rapid antibiotic susceptibility test (AST) could reliably detect antibiotic resistance to the four drugs in 60 minutes, and the results were highly concordant with the conventional AST for detection of ceftriaxone, cefepime, meropenem, and ciprofloxacin resistance with a high accuracy of 99%, 96%, 96%, and 93%, respectively. Therefore, the rapid AST established in our study helps enable targeted therapy to reduce the empirical use of antibiotics and ultimately the health and economic burdens of antibiotic resistance.